Price Perception and Patient Experience Influence Word of Mouth, Mediated by Integrity in Biak Hospital - Eka Dara Sakti Pratiwi; , Endang Ruswanti; Idrus Jus’at (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The decreasing number of visits is a problem for hospitals. Word of mouth (WOM) advertising plays an important role in business development in the health sector. This study aims to analyze the effect of price perception and patient experience on word of mouth with integrity as an intervening variable in patients at Lanud Manuhua Biak Hospital. The study used a quantitative causality design that analyzed the causal influence along with descriptive analysis using the threebox method. Respondents consisted of 200 hospital patients. The sampling method used purposive sampling. The data analysis method used PLS SEM. The results of the study found that there was a simultaneous effect of price perception and patient experience on word of mouth through integrity mediation. Price perception has a positive effect on word of mouth. Patient experience has a positive effect on word of mouth. Price perception has a positive effect on integrity. Patient experience has a positive effect on integrity. Integrity has a positive effect on word of mouth. Hospitals are expected to improve the quality of services provided in accordance with the prices that have been set, such as adding chairs, providing information about doctors' delays, simplifying the bureaucratic service process, training doctors to be more willing to listen to patients and sincerely serve their patients, shortening waiting hours, adding facilities in the waiting room.